Wireless Monitoring System for Off-Grid PV Systems Based on Raspberry Pi - Muhammad Dafa Alfaruqj; Ali Basrah Pulungan (Jurnal Teknik Elektro Indonesia, 2026)
The use of renewable energy such as Solar Power Plants (PLTS) is growing in various regions, especially in remote areas that are not reached by conventional power grids. However, off-grid solar systems require periodic monitoring to keep them functioning optimally. This study aims to design a wireless monitoring system for off-grid solar power plants by utilizing Raspberry Pi as a data processing center, monitoring important parameters such as current, voltage, power, temperature, humidity and light intensity at regular intervals. The method used involves ESP8266 as a sensor data transmitter node through the MQTT communication protocol. Node-RED acts as a data bridge between MQTT and Raspberry Pi, which then stores the data into a MySQL Database and is visualized through the Grafana dashboard. The test results show that the system is able to display sensor data periodically, accurately, and informatively, as well as facilitate the process of analyzing the performance of the Off-grid PV system. Thus, this system can be an effective and efficient monitoring solution for the implementation of solar power plants in remote locations.